ANALISIS EXEPERIMENTAL VARIASI KECEPATAN SUDUT DAN VARIASI UKURAN PAKAN TERHADAP PERFORMANSI MESIN PENEBARAN PAKAN IKAN - Naili Saidatin; Denni kurniawan; Hasan Syafik Maulana (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2022)
ABSTRACTThe development of technology for fish feed spreader machine has developed tremendously. Indonesia which belongs to country with strong culture including in the fishery has rich and potential sources of fishery in terms of sea, public, and culture fisheries. The activity of manual fish feeding sometimes get lateness, different feed portion, and schedule discrepancy due to other works or forgetfulness. Automatic fish feeding can distribute the feed in the measurable number so that efficiency can be improved and the fish culture can satisfy the target. The development of such device aims at testing the performance of machine that can throw scheduled-fish feed. Therefore, this research conducted observation on the effects of angular velocity against the spread pattern of fish feed. The optimum velocity against the rpm effect occurred in the feed type 1-2 mm and 2-3 mm within the blade model 5. The farthest distances at 500 rpm, 1000 rpm, and 1500 rpm yielded 3.8 m, 4.5 m, and 5.6 m consecutively. Furthermore, the feed distribution averages for the size 1-2 mm at 500 rpm, 1000 rpm, and 1500 rpm gained 20 %, 25%, and 17% sequentially. The feed size 2-3 mm generated average rpm by 21%, 23%, and 20% at 500 rpm, 1000 rpm, and 1500 rpm respectively.